Electrode plate and preparation method and application thereof
By adding silane-modified carbon nanotubes of different lengths to the electrode slurry, multi-layer coating is performed to form a tree-shaped conductive network structure with gradient distribution, the problem of low conductivity and diffusion rate of lithium iron phosphate batteries is solved, and the rate performance and cycle stability of the battery are improved.
Patent Information
- Application Number
- CN202510286177.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-11
- Publication Date
- 2025-06-10
AI Technical Summary
Due to the limited crystal structure of lithium iron phosphate batteries, low electronic conductivity and low Li+ diffusion rate, resulting in low actual specific capacity and poor high-rate performance, making it difficult to meet the market's demand for fast charging performance of lithium-ion batteries.
By adding silane-modified carbon nanotubes of different lengths to the electrode slurry, multi-layer coating is performed to form a tree fork-shaped conductive network structure with gradient distribution, optimize the transmission path, and improve ion and electron conductivity.
It improves the battery's rate performance and cycle stability, and enhances the fast charging and circulation capabilities of lithium iron phosphate batteries.
Smart Images

Figure BDA0005307453350000121 
Figure BDA0005307453350000131 
Figure HDA0005307453440000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and more specifically, to an electrode sheet, a preparation method thereof, and an application thereof. Background Art
[0002] Lithium iron phosphate has the advantages of low price, high theoretical capacity, long cycle life, excellent cycling performance, good structural thermal stability during the lithium ion insertion and extraction process, etc. However, due to the limitation of its own crystal structure, the FeO 6 octahedra sharing vertices are separated by PO 4 tetrahedra, and there is no continuous FeO 6 edge-sharing octahedron network. Electrons can only conduct through Fe-O-Fe, and the electronic conductivity is only 10 - 9 S / cm. At the same time, the PO 6 tetrahedra located between the LiO 6 octahedra and the FeO 4 octahedra limit the movement space of Li + , resulting in a low Li + diffusion rate, only 1.8×10 -16 ~2.2×10 -14 cm 2 / s, leading to a low actual specific capacity and poor high-rate performance.
[0003] In order to meet the market demand for the fast charging performance of lithium ion batteries, so far, people have done a lot of research work in aspects such as nanosizing, coating, and doping modification of lithium iron phosphate materials, and achieved good results. Lithium iron phosphate materials have been put into practical applications. Currently, it is necessary to further optimize the electrode sheet hierarchical structure and formulation, optimize the Li ion insertion and extraction channels, reduce the tortuosity, so as to improve the ion transport efficiency of the electrode sheet and the fast charging performance of the battery. Summary of the Invention
[0004] In view of this, the purpose of the present invention is to provide an electrode sheet, a preparation method thereof, and an application thereof. By adding silane-modified carbon nanotubes with different defined conditions to the slurry and performing two-layer or more coating, the requirement for the refined improvement of the electrode sheet structure hierarchy is met, and the battery performance is improved.
[0005] The present invention provides an electrode sheet, which includes a current collector and an active material layer. The active material layer is disposed on at least a part of the surface of at least one side of the current collector. The active material layer includes two sub-active material layers in the thickness direction. Among them, the first sub-active material layer is disposed on the surface of the current collector, and the second sub-active material layer is disposed on the surface of the first sub-active material layer. Both of the two sub-active material layers contain silane-modified carbon nanotubes, and the length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than that in the first sub-active material layer.
[0006] Preferably, the active material layer further includes a third sub-active material layer, and the third sub-active material layer is disposed on the surface of the second sub-active material layer. The length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than that in the first sub-active material layer and the third sub-active material layer; or, the length of the silane-modified carbon nanotubes in the second sub-active material layer is less than that in the third sub-active material layer and greater than that in the first sub-active material layer.
[0007] Preferably, the thickness of the third sub-active material layer accounts for 25% - 30% of the thickness of the active material layer; the thickness of the second sub-active material layer accounts for 40% - 50% of the thickness of the active material layer; the thickness of the first sub-active material layer accounts for 25% - 30% of the thickness of the active material layer.
[0008] Preferably, the electrode sheet is a positive electrode sheet. The content of the silane-modified carbon nanotubes in the third sub-active material layer of the positive electrode sheet is 0.2% - 2%, and the length is 100 nm - 2800 nm; the content of the silane-modified carbon nanotubes in the second sub-active material layer of the positive electrode sheet is 0.4% - 2%, and the length is 100 nm - 3000 nm; the content of the silane-modified carbon nanotubes in the first sub-active material layer of the positive electrode sheet is 0.2% - 2%, and the length is 100 nm - 2800 nm.
[0009] Preferably, the electrode sheet is a negative electrode sheet. The content of the silane-modified carbon nanotubes in the third sub-active material layer of the negative electrode sheet is 0.2% - 2.5%, and the length is 100 nm - 3000 nm; the content of the silane-modified carbon nanotubes in the second sub-active material layer of the negative electrode sheet is 0.4% - 2.5%, and the length is 100 nm - 3000 nm; the content of the silane-modified carbon nanotubes in the first sub-active material layer of the negative electrode sheet is 0.2% - 2.5%, and the length is 100 nm - 3000 nm.
[0010] Preferably, the silane-modified carbon nanotubes include carbon nanotubes and a silane coupling agent coating at least a part of the surface of the carbon nanotubes, and the silane coupling agent is covalently bonded to the carbon nanotubes;
[0011] The mass ratio of the carbon nanotubes to the silane coupling agent is (1.25 - 3.6):1.
[0012] Preferably, the carbon nanotubes have a length of 100 nm to 5000 nm and a diameter of 2 nm to 60 nm.
[0013] Preferably, the silane coupling agent includes one or more of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 1H,1H,2H,2H-perfluorododecyltrimethoxysilane, 1H,1H,2H,2H-perfluorododecyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane.
[0014] The present invention also provides a method for preparing the electrode sheet described in the above technical solution, including the following steps:
[0015] Prepare a variety of electrode slurries, and make the variety of electrode slurries contain silane-modified carbon nanotubes;
[0016] Coat the variety of electrode slurries on at least a part of the surface of at least one side of the current collector in the thickness direction of the current collector to form an active material layer including a plurality of sub-active material layers, and obtain the electrode sheet after drying and pressing;
[0017] Each of the electrode slurries includes an active material, a binder, silane-modified carbon nanotubes, and a solvent.
[0018] The present invention also provides a lithium battery including the electrode sheet described in the above technical solution.
[0019] The present invention provides an electrode sheet, a preparation method thereof, and an application; the electrode sheet includes a current collector and an active material layer, the active material layer is provided on at least a part of the surface of at least one side of the current collector, the active material layer includes two sub-active material layers in the thickness direction, wherein the first sub-active material layer is provided on the surface of the current collector, and the second sub-active material layer is provided on the surface of the first sub-active material layer; both of the two sub-active material layers contain silane-modified carbon nanotubes, and the length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer. Compared with the prior art, by adding silane-modified carbon nanotubes with different lengths to the slurry and performing multi-layer coating, the present invention can meet the requirements for fine improvement of the electrode structure level and improve the battery performance; thereby forming a gradient-distributed dendritic conductive network structure, optimizing the transmission path, improving the ion and electron conductivity, and at the same time, the modified carbon nanotubes play a role in supporting and protecting the material, ultimately improving the battery rate performance and cycle stability, and achieving the purpose of enhancing the fast charging and cycling ability of the lithium iron phosphate battery.
[0020] Meanwhile, the overall process route of the preparation method provided by the present invention is clear and concise, the conditions are easy to control, and it has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 It is a schematic diagram of the surface silane modification of carbon nanotubes in the embodiment of the present invention;
[0022] Figure 2 It is a schematic diagram of the electrode sheet provided by the embodiment of the present invention;
[0023] Figure 3 It is the rate discharge test results of each embodiment and comparative example of the present invention;
[0024] Figure 4 It is the cycle test results of each embodiment and comparative example of the present invention. DETAILED DESCRIPTION OF THE INVENTION
[0025] Next, in combination with the embodiments of the present invention, the technical solutions of the present invention will be clearly and completely described. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts fall within the protection scope of the present invention.
[0026] The present invention provides an electrode sheet, which includes a current collector and an active material layer. The active material layer is provided on at least a part of the surface of at least one side of the current collector. The active material layer includes two sub-active material layers in the thickness direction. Among them, the first sub-active material layer is provided on the surface of the current collector, and the second sub-active material layer is provided on the surface of the first sub-active material layer; both of the two sub-active material layers contain silane-modified carbon nanotubes, and the length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer.
[0027] The present invention relates to the technical field of secondary batteries. Specifically, the multi-layer coating technology of the electrode sheet is implemented. In the preferred embodiment of the present invention, first, the purchased carbon nanotubes (hereinafter referred to as CNT) are subjected to surface activation treatment, and then the activated CNT and the silane coupling agent are prepared into silane-modified CNT through a liquid-phase reaction. Then, the above-mentioned silane-modified CNT is added to the positive and negative electrode slurries according to a certain ratio to obtain a mixed slurry, and finally, the electrode sheet is prepared through layered coating.
[0028] In the present invention, the active material layer includes two sub-active material layers in the thickness direction, wherein the first sub-active material layer is disposed on the surface of the current collector, and the second sub-active material layer is disposed on the surface of the first sub-active material layer; preferably, a third sub-active material layer is further included, that is, the active material layer includes three sub-active material layers, and the third sub-active material layer is disposed on the surface of the second sub-active material layer and preferably contacts the separator.
[0029] In the present invention, the above-mentioned multiple sub-active material layers all contain silane-modified carbon nanotubes, and the lengths of the silane-modified carbon nanotubes in adjacent sub-active material layers are different. Taking two sub-active material layers as an example, the length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer.
[0030] In a preferred embodiment of the present invention, the length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer and the third sub-active material layer; the long CNTs have better intertwining and coating effects, which is beneficial to stabilizing the structure of the second sub-active material layer (intermediate layer). During the rolling process, the pressure can be effectively conducted to the materials of the first sub-active material layer and the third sub-active material layer, which helps to improve compaction and thus increase the energy density; the first sub-active material layer and the third sub-active material layer (upper and lower layers) use short CNTs, which have a more complex intertwined conductive network compared to long CNTs, greatly improving the conductivity. At the same time, the area coated with the silane coupling agent is larger, and the corrosion resistance is stronger, effectively improving the cycle performance of the material.
[0031] In another preferred embodiment of the present invention, the length of the silane-modified carbon nanotubes in the second sub-active material layer is less than the length of the silane-modified carbon nanotubes in the third sub-active material layer (upper layer) and greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer (lower layer); adopting the above design of directional gradient distribution is more conducive to pressure conduction and improving compaction.
[0032] In the present invention, the thickness of the third sub-active material layer preferably accounts for 25% - 30% of the thickness of the active material layer; the thickness of the second sub-active material layer preferably accounts for 40% - 50% of the thickness of the active material layer; the thickness of the first sub-active material layer preferably accounts for 25% - 30% of the thickness of the active material layer.
[0033] On this basis, a thicker second sub-active material layer with long CNTs helps improve the battery capacity retention rate and cycling performance; a thinner third sub-active material layer with short CNTs can promote the rapid diffusion of Li ions to the second and first sub-active material layers, slightly improving the fast charging performance. At the same time, the coated surface will be flatter than that of long CNTs, reducing the contact impedance between the electrode and the separator (in contact with the third sub-active material layer); a thinner first sub-active material layer with short CNTs mainly improves the bonding effect between the electrode and the current collector (in contact with the first sub-active material layer), reduces the probability of material pulverization and shedding, plays a supporting and conductive role for the second sub-active material layer, and alleviates the structural changes of the positive and negative electrode materials during the lithium insertion and extraction process.
[0034] In a preferred embodiment of the present invention, the electrode sheet is a positive electrode sheet (i.e., the cathode of the lithium battery); the content of silane-modified carbon nanotubes in the third sub-active material layer (upper layer) of the positive electrode sheet is preferably 0.2% - 2%, more preferably 0.8% - 1.5%, and the length is preferably 100nm - 2800nm, more preferably 200nm - 800nm; the content of silane-modified carbon nanotubes in the second sub-active material layer (middle layer) of the positive electrode sheet is preferably 0.4% - 2%, more preferably 1.3% - 1.8%, and the length is preferably 100nm - 3000nm, more preferably 1000nm - 2500nm; the content of silane-modified carbon nanotubes in the first sub-active material layer (lower layer) of the positive electrode sheet is preferably 0.2% - 2%, more preferably 0.8% - 1.5%, and the length is preferably 100nm - 2800nm, more preferably 200nm - 800nm.
[0035] In another preferred embodiment of the present invention, the electrode sheet is a negative electrode sheet (i.e., the anode of the lithium battery); the content of silane-modified carbon nanotubes in the third sub-active material layer (upper layer) of the negative electrode sheet is preferably 0.2% - 2.5%, more preferably 0.8% - 1.6%, and the length is preferably 100nm - 3000nm, more preferably 200nm - 600nm; the content of silane-modified carbon nanotubes in the second sub-active material layer (middle layer) of the negative electrode sheet is preferably 0.4% - 2.5%, more preferably 1.2% - 2.2%, and the length is preferably 100nm - 3000nm, more preferably 800nm - 2200nm; the content of silane-modified carbon nanotubes in the first sub-active material layer (lower layer) of the negative electrode sheet is preferably 0.2% - 2.5%, more preferably 0.8% - 1.6%, and the length is preferably 100nm - 3000nm, more preferably 200nm - 600nm.
[0036] In the present invention, for the three-layer case, it is preferred that the CNT length and content in the second sub-active material layer are relatively high (more preferably > 1000 nm, > 1.3%), and short CNTs (more preferably 200 nm to 600 nm) are selected for the first sub-active material layer and the third sub-active material layer. In addition, although the influence of the content limit is small, it also has a certain influence on the overall performance.
[0037] In the present invention, the silane-modified carbon nanotubes preferably include carbon nanotubes and a silane coupling agent coating at least a part of the surface of the carbon nanotubes, and the silane coupling agent is preferably connected to the carbon nanotubes by a covalent bond; the mass ratio of the carbon nanotubes to the silane coupling agent is preferably (1.25 to 3.6):1, specifically, it can be 1.25:1, 1.5:1, 2:1, 2.5:1, 3:1, 3.6:1. If there is too much silane coupling agent, it will completely cover the surface of the CNTs, resulting in a significant reduction in conductivity. If there is too little silane coupling agent, the coating will be uneven and it will not play a role in promoting dispersion and corrosion resistance. Therefore, it can be seen that the molecular-level surface modification has a great influence on the performance of carbon nanotube materials, and the qualitative change process is obvious.
[0038] In the present invention, the length of the carbon nanotubes is preferably 100 nm to 5000 nm, and the diameter is preferably 2 nm to 60 nm. The present invention has no special restrictions on the source of the carbon nanotubes, and commercially available products well-known to those skilled in the art can be used.
[0039] In the present invention, the silane coupling agent preferably includes one or more of 1H,1H,2H,2H-perfluorooctyltrimethoxysilane, 1H,1H,2H,2H-perfluorooctyltriethoxysilane, 1H,1H,2H,2H-perfluorododecyltrimethoxysilane, 1H,1H,2H,2H-perfluorododecyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane. The present invention has no special restrictions on the source of the silane coupling agent, and commercially available products well-known to those skilled in the art can be used.
[0040] In the present invention, the electrode sheets (including the positive and negative electrode sheets) are required to have the characteristics of high-rate charge and discharge with stable structure, high electron and ion conductivity, and corrosion resistance to by-products in the electrolyte. As a one-dimensional carbon material, CNTs have good electrical conductivity, and the aspect ratio is usually greater than 100, which is easy to form an interlaced conductive network, enhancing conductivity and structural stability. At the same time, modifying its surface to improve its corrosion resistance can be added to the slurry as a conductive agent, stabilizer and corrosion-resistant additive to improve the battery rate and cycle performance. The present invention can efficiently and simply optimize the battery electrode sheets by refining the CNT modification strategy and optimizing the types and contents of modified CNTs in different layers of electrode sheets, providing a reliable solution for promoting the fast charging performance of lithium iron phosphate batteries.
[0041] The present invention also provides a method for preparing the electrode sheet described in the above technical solution, including the following steps:
[0042] Prepare a variety of electrode slurries, and make the variety of electrode slurries contain silane-modified carbon nanotubes;
[0043] Coat the variety of electrode slurries on at least a part of the surface of at least one side of the current collector in the thickness direction of the current collector in turn to form an active material layer including a plurality of sub-active material layers, and obtain the electrode sheet after drying and pressing;
[0044] Each of the electrode slurries includes an active material, a binder, silane-modified carbon nanotubes, and a solvent.
[0045] The present invention has no special limitation on the preparation process of the electrode slurry. The technical means of adding an active material, a binder, and silane-modified carbon nanotubes into a solvent and stirring evenly to form a mixed slurry well-known to those skilled in the art can be adopted.
[0046] In the present invention, the silane-modified carbon nanotubes are preferably obtained by successively modifying carbon nanotubes by Fenton oxidation method and silane surface modification.
[0047] In the present invention, the preparation method of the silane-modified carbon nanotubes is preferably specifically as follows:
[0048] (1) Modification of CNT raw materials: The present invention uses the Fenton oxidation method for modification. Disperse the commercially available initial CNT in solution A with a volume ratio of alcohol to water of 1:(0.5 - 1.5), stir evenly, add a weak acid to adjust the pH of the solution to between 4.5 and 5.5, use an ultrasonic crusher (upper limit power 800W) to fully disperse the CNT, set the instrument power to 40% - 80%, crush for 2s - 5s, stop for 1s - 3s, and last for 2min - 10min in total to ensure the CNT is evenly dispersed. Add 1 - 5 times the mass of Fe of CNT 2+ source to the solution, stir for 15min - 30min, and slowly drip solution B with a volume ratio of hydrogen peroxide to water of 1:(1 - 5) equal to its mass into solution A while stirring. The dropping duration is 0.5h - 2.5h. Then filter the material by suction, wash the solution with alcohol until neutral, and finally place the material in a vacuum oven at 60°C - 80°C for drying to obtain CNT materials with hydroxyl groups on the surface.
[0049] (2) CNT surface modification with silane: Mix the CNT material with hydroxyl groups on its surface, silane coupling agent, and alcohol in a mass ratio of (0.5 - 2):(0.1 - 1.5):(50 - 100) evenly. Then add weak acid to adjust the pH to between 4 and 5, stir for 15 min - 45 min to disperse evenly. Raise the temperature of the system to 45°C - 120°C, carry out condensation reflux stirring for 1 h - 6 h. Then filter the material, wash it with alcohol and water multiple times until the solution reaches neutral. Finally, place the material in a vacuum oven at 45°C - 100°C to dry, and obtain silane-modified CNT.
[0050] In the present invention, the carbon nanotubes and the silane coupling agent are the same as those described in the above technical solution, and will not be elaborated here.
[0051] In the present invention, the alcohol preferably includes one or more of methanol, ethanol, isopropanol, and ethylene glycol, and more preferably ethanol. The present invention has no special restrictions on the source of the alcohol, and commercially available products well-known to those skilled in the art can be used.
[0052] In the present invention, the Fe 2+ source preferably includes one or more of ferrous sulfate, ferrous acetate, ferrous carbonate, ferrous nitrate, and ferrous chloride, and more preferably ferrous sulfate. The present invention has no special restrictions on the source of the Fe 2+ source, and commercially available products well-known to those skilled in the art can be used.
[0053] In the present invention, the weak acid preferably includes one or more of acetic acid, carbonic acid, citric acid, and malic acid, and more preferably acetic acid. The present invention has no special restrictions on the source of the weak acid, and commercially available products well-known to those skilled in the art can be used.
[0054] In the present invention, for silane modification (different types of silane modification can be used for the upper, middle, and lower layers, and the performance difference is not significant), a silane coupling agent with a larger silane chain length is preferably used, which can bind more firmly on the CNT surface. At the same time, a silane coupling agent with F element is preferably used, which can improve the anti-corrosion effect.
[0055] The present invention uses the above preparation method to obtain silane-modified carbon nanotubes. First, the CNT surface is activated: There are certain groups (hydroxyl groups, carboxyl groups, etc.) on the initial CNT surface, but they are not sufficient for comprehensive grafting of silane and need to be pretreated. The Fenton reaction uses hydrogen peroxide and Fe 2+ to react to generate hydroxyl radicals -OH with strong oxidation ability (high electronegativity / electrophilicity), which have strong addition reaction characteristics and form a large number of hydroxyl groups on the material surface. Then, the alkane surface is modified: In the prior art, the general formula of the silane coupling agent is RSiX 3, where R represents an active functional group having an affinity or reactivity with the polymer molecule, such as an oxy group, a mercapto group, a vinyl group, an epoxy group, an amide group, an aminopropyl group, etc., and X represents an alkoxy group capable of hydrolysis, such as a halogen, an alkoxy group, an acyloxy group; during coupling, first the X group hydrolyzes to form silanol -Si-OH, and then reacts with -OH on the CNT surface to form a hydrogen bond and condenses into a Si-O-C covalent bond (C represents the CNT surface); at the same time, the silanols -Si-OH of each silane molecule associate with each other and oligomerize to form a network-structured film covering the material surface, which helps to reduce the surface energy of CNTs and promotes the uniform dispersion of CNTs in the slurry. The above preparation method is a molecular-level coating modification, which does not change the one-dimensional structure and high conductivity characteristics of CNTs themselves. At the same time, a large number of F atoms on the R group of the silane can improve its acid corrosion resistance.
[0056] The present invention adds the above-modified CNTs to the positive and negative electrode slurries to form an interwoven conductive network between the gaps and the surface of the large particles. Due to the excellent physical properties of CNTs, such a conductive network can form an effect similar to that of a fishing net, playing a certain isolation and restriction role between different coatings, which helps to hierarchically construct specific functional layers.
[0057] After that, the present invention coats the above-mentioned various electrode slurries on at least a part of the surface of at least one side of the current collector along the thickness direction of the current collector to form an active material layer including a plurality of sub-active material layers, and obtains the electrode sheet after drying and pressing.
[0058] In the present invention, the electrode slurries all include an active material, a binder, silane-modified carbon nanotubes, and a solvent.
[0059] In the present invention, the active material can be selected as either a positive electrode active material or a negative electrode active material. When using a positive electrode active material, the solvent is preferably NMP, and a positive electrode sheet is further prepared; when using a negative electrode active material, the solvent is preferably water, and a negative electrode sheet is further prepared.
[0060] The present invention places no special restrictions on the types and sources of the positive electrode active material, the negative electrode active material, and the binder, and commercially available active materials well-known to those skilled in the art for preparing positive and negative electrode sheets of lithium batteries can be used.
[0061] In a preferred embodiment of the present invention, the electrode sheet is a positive electrode sheet: the positive electrode active material, the binder, and the silane-modified carbon nanotubes are added to the solvent NMP in a mass ratio of (95 - 99):(0.8 - 3.0):(0.2 - 2.0), stirred evenly to form a uniform and stable slurry, extrusion-coated on the foil, dried to obtain a positive electrode roll, roll-pressed to obtain a single-coated positive electrode sheet, and then coated with multiple layers of materials in the same steps. Finally, the total coating weight is 220 g / m 2~240 g / m 2 , a composite positive electrode sheet for a lithium battery is obtained.
[0062] In another preferred embodiment of the present invention, the electrode sheet is a negative electrode sheet: negative active material, binder, and silane-modified carbon nanotubes are added to water in a mass ratio of (93 - 98):(0.5 - 4.5):(0.2 - 2.5), stirred to form a uniform and stable slurry, extrusion-coated onto a foil, dried to obtain a negative roll, roll-pressed to obtain a single-coated negative electrode sheet, and then multiple layers of materials are coated in the same steps. The final coating weight is 110 g / m 2 ~130 g / m 2 , a composite negative electrode sheet for a lithium battery is obtained.
[0063] In the present invention, the foil can be selected from the conventional foils for preparing positive and negative electrode sheets well-known to those skilled in the art, commercially available, and the present invention has no special restrictions thereon; the coating process used can be the conventional coating means for preparing positive and negative electrode sheets well-known to those skilled in the art.
[0064] The present invention also provides a lithium battery, including the electrode sheet described in the above technical solution, and this electrode sheet can be used as the positive electrode and / or the negative electrode.
[0065] In the present invention, for different types of lithium batteries, corresponding raw materials for preparing lithium batteries well-known to those skilled in the art, such as diaphragms (such as PP, PE, PET, PA, etc. well-known to those skilled in the art), electrolytes, etc., are used to obtain corresponding products according to the conventional technical means for preparing lithium batteries, and the present invention has no special restrictions thereon.
[0066] The present invention has the following beneficial effects:
[0067] Through surface molecular-level modification of CNT, the present invention can improve its dispersibility in the slurry without changing the inherent properties of CNT. At the same time, CNT modification can form an intertwined conductive network, improve conductivity, protect particles from acid corrosion, and finally form a fishnet-like CNT layer.
[0068] By changing the limiting conditions such as the length of CNT between different layers, the present invention can simply construct a coating with specific functions. At the same time, by further optimizing the CNT content and modification between different layers, the rate performance and cycle performance of the battery can be improved.
[0069] The present invention provides an electrode sheet, a preparation method thereof and an application; the electrode sheet includes a current collector and an active material layer, the active material layer is provided on at least a part of the surface on at least one side of the current collector, the active material layer includes two sub-active material layers in the thickness direction, wherein the first sub-active material layer is provided on the surface of the current collector, and the second sub-active material layer is provided on the surface of the first sub-active material layer; both of the two sub-active material layers contain silane-modified carbon nanotubes, and the length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer. Compared with the prior art, by adding silane-modified carbon nanotubes with different lengths to the slurry and performing multi-layer coating, the present invention can meet the requirements for fine improvement of the electrode sheet structure level and improve the battery performance; thereby forming a gradient-distributed dendritic conductive network structure, optimizing the transmission path, improving the ion and electron conductivity, and at the same time, the modified carbon nanotubes play a role in supporting and protecting the material, ultimately improving the battery rate performance and cycle stability, and achieving the purpose of enhancing the fast charging and cycling ability of the lithium iron phosphate battery.
[0070] Meanwhile, the preparation method provided by the present invention has a clear and concise overall process route, easy-to-control conditions, and broad application prospects.
[0071] To further illustrate the present invention, the following detailed description is provided through the following examples. All raw materials used in the following examples of the present invention are commercially available. Among them, 1H,1H,2H,2H-perfluorooctyltrimethoxysilane is designated as A, 1H,1H,2H,2H-perfluorooctyltriethoxysilane is designated as B, 1H,1H,2H,2H-perfluorododecyltrimethoxysilane is designated as C, 1H,1H,2H,2H-perfluorododecyltriethoxysilane is designated as D, and heptadecafluorodecyltrimethoxysilane is designated as E.
[0072] Example 1
[0073] First, disperse CNT in solution A with an ethanol:water ratio of 1:1 (volume ratio), stir evenly, add a weak acid (acetic acid) to adjust the pH of the solution to 5, and use an ultrasonic crusher to fully disperse CNT. The instrument power is set to 60%, crush for 4 s, stop for 2 s, and continue for a total of 8 min to ensure uniform dispersion of CNT.
[0074] Add ferrous sulfate with 4 times the mass of CNT to the solution, stir for 30 min, and slowly drop solution B with a hydrogen peroxide:water volume ratio of 1:4 equal to its mass into solution A while stirring. The dropping duration is 2 h; then filter the material, wash the solution with ethanol until neutral, and finally place the material in a vacuum oven at 80 °C for drying to obtain CNT material with hydroxyl groups on the surface.
[0075] CNT Surface Silane Modification: Mix the above-activated CNT, silane E, and ethanol evenly according to a mass ratio of 1.5:0.5:80. Then add acetic acid to adjust the pH to 4.5, stir for 30 min to disperse evenly, raise the system temperature to 80 °C, condense and reflux with stirring for 4.5 h. Then filter the material, wash it multiple times with water containing ethanol until the solution reaches neutrality. Finally, place the material in a vacuum oven at 60 °C for drying to obtain the surface-modified CNT material; for the schematic diagram, see Figure 1 as shown.
[0076] For the positive electrode plate: Add the positive electrode active material, binder, and CNT conductive agent to the solvent NMP, stir evenly to form a uniform and stable slurry, extrude and coat it on the foil, and obtain a positive electrode roll after drying. After rolling, obtain a coated positive electrode plate. Then coat two layers of materials in the same steps. Finally, the total coating weight is 240 g / m 2 .
[0077] For the negative electrode plate: Add the negative electrode active material, binder, and CNT conductive agent to water, stir to form a uniform and stable slurry, extrude and coat it on the foil, and obtain a negative electrode roll after drying. After rolling, obtain a coated negative electrode plate. Then coat two layers of materials in the same steps. Finally, the coating weight is 120 g / m 2 .
[0078] Specifically, the conditions and parameters of the three-layer coating materials refer to Table 1. The middle layer is composed of longer CNTs, and the content is also the largest among the three layers. The upper and lower layers select shorter CNTs; for the schematic diagram, see Figure 2 as shown.
[0079] Example 2
[0080] The difference from Example 1 is that the modified silane is changed from E to C, and the rest remains unchanged; to verify the feasibility of different silane modifications.
[0081] Example 3
[0082] The difference from Example 1 is that the modified silane is changed from E to A, and the length and content of CNTs gradually decrease from top to bottom in the three-layer coating, forming a directional gradient distribution, and the rest remains unchanged.
[0083] Example 4
[0084] The difference from Example 1 is that the upper, middle, and lower layers of CNTs are modified with silanes E, C, and A respectively, and the rest remains unchanged; to verify the feasibility of silane stratification.
[0085] Comparative Example 1
[0086] Different from Example 1, the upper and lower layers are changed to those with a large CNT content and length, and the middle layer has a small CNT content and short length, with the rest unchanged; to explore the influence of the sandwich structure.
[0087] Comparative Example 2
[0088] Different from Example 1, the modified silane is changed from E to A, and the CNT length and content gradually increase from top to bottom in the three-layer coating, forming a directional gradient distribution, with the rest unchanged; thus forming a contrast with Example 3.
[0089] Comparative Example 3
[0090] Different from Example 1, the CNT is not activated and modified with silane, with the rest unchanged; to prove the positive effect of silane modification.
[0091] Comparative Example 4
[0092] Different from Example 1, during the CNT modification process, CNT / silane / ethanol = 2.0 / 0.5 / 80, with the rest unchanged; to verify the influence of the silane coating amount on CNT on the performance.
[0093] Specifically, for the three-layer coating material, refer to Table 1. The middle layer is composed of longer CNTs, and at the same time, the content is the largest among the three layers. The upper and lower layers are selected with shorter CNTs.
[0094] Table 1 Three-layer coating parameters
[0095]
[0096]
[0097] Perform various performance tests on the electrode sheets provided in each example and comparative example, specifically including:
[0098] (1) For the positive electrode sheet and the negative electrode sheet, they are obtained according to the above technical solution.
[0099] (2) The separator is a polypropylene-based film with a base film thickness of 7 μm, double-sided coated with a 3-μm PVDF, and then gravure-coated with 3 μm of alumina.
[0100] (3) During the cell assembly process: Arrange the positive electrode sheet, separator, and negative electrode sheet in sequence, and the winding method is adopted for assembly.
[0101] (4) The electrolyte is LiPF 6 dissolved in a solvent with a ratio of ethylene carbonate, ethyl methyl carbonate, and diethyl carbonate of 1.5:1:0.5, with a concentration of 1.2 mol / L.
[0102] (5) Inject the electrolyte into the dry cell, and obtain a lithium-ion soft-pack battery after formation and grading.
[0103] (6) Discharge rate test:
[0104] In a 25 °C incubator, charge at a constant current of 0.33C to 3.65V, then charge at a constant voltage of 3.65V until the current reaches 0.05C. After standing for 30 minutes, discharge at a constant current of 0.33C to 2.5V, then stand. Cycle the battery three times, and take the capacity of the last week as the actual capacity C0 of the battery. Charge at a constant current of 0.33C0 to 3.65V, then charge at a constant voltage of 3.65V until the current reaches 0.05C. Then discharge to 2.5V at rates of 0.33C0, 0.5C0, 1C0, and 2C0 respectively, and stand to obtain the discharge capacities of the battery at different rates.
[0105] The test results are shown in Figure 3 as follows.
[0106] (7) Cycle test:
[0107] In a 25 °C incubator, charge at a constant current of 0.33C to 3.65V, then charge at a constant voltage of 3.65V until the current reaches 0.05C. After standing for 30 minutes, discharge at a constant current of 0.33C to 2.5V, then stand. Cycle the battery three times, and take the capacity of the last week as the actual capacity C0 of the battery. Charge and discharge the battery at 1C / 1C, compare the capacity of each cycle with that of the first cycle to obtain the cycle capacity retention rate. Stop cycling when the capacity reaches 0.8*C0, and record the number of cycles.
[0108] The test results are shown in Figure 4 as follows.
[0109] The experimental results show that in Example 1, the long CNTs have a better effect of interweaving and coating, which is beneficial to stabilizing the intermediate layer structure. During the rolling process, the pressure can be effectively conducted to the lower layer materials, helping to improve compaction and thus increasing the energy density. The short CNTs are used in the upper and lower layers, which have a more complex interwoven conductive network compared to the long CNTs, resulting in a significant improvement in conductivity. At the same time, the area coated with silane is larger and the corrosion resistance is stronger, effectively improving the cycling performance of the material. While in Example 2, the design of directional gradient distribution is more conducive to pressure conduction and improving compaction.
[0110] By adding different types and contents of silane-modified CNTs to the slurry in the present invention, after three-layer coating, the requirements for fine improvement of the electrode structure hierarchy can be met, and the battery performance can be improved. Thus, a gradient-distributed dendritic conductive network structure is formed, optimizing the transmission path, improving the ion and electron conductivity. At the same time, the modified CNTs play a role of supporting and protecting the material, ultimately improving the battery rate performance and cycling stability, and achieving the purpose of enhancing the fast charging and cycling ability of the lithium iron phosphate battery.
[0111] The foregoing description of the disclosed embodiments enables those skilled in the art to practice or use the present invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Thus, the present invention is not intended to be limited to the embodiments shown herein but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. An electrode sheet, characterized in that: It includes a current collector and an active material layer, wherein the active material layer is arranged on at least a portion of the surface of at least one side of the current collector, and the active material layer includes two sub-active material layers along the thickness direction, wherein the first sub-active material layer is arranged on the surface of the current collector, and the second sub-active material layer is arranged on the surface of the first sub-active material layer; the two sub-active material layers both contain silane-modified carbon nanotubes, and the length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer.
2. The electrode sheet according to claim 1, characterized in that: The active material layer also includes a third sub-active material layer, which is arranged on the surface of the second sub-active material layer; the length of the silane-modified carbon nanotubes in the second sub-active material layer is greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer and the third sub-active material layer; or, the length of the silane-modified carbon nanotubes in the second sub-active material layer is less than the length of the silane-modified carbon nanotubes in the third sub-active material layer and greater than the length of the silane-modified carbon nanotubes in the first sub-active material layer.
3. The electrode sheet according to claim 2, characterized in that: The thickness of the third sub-active material layer accounts for 25% to 30% of the thickness of the active material layer; the thickness of the second sub-active material layer accounts for 40% to 50% of the thickness of the active material layer; the thickness of the first sub-active material layer accounts for 25% to 30% of the thickness of the active material layer.
4. The electrode sheet according to claim 2, characterized in that: The electrode sheet is a positive electrode sheet; the content of silane-modified carbon nanotubes in the third sub-active material layer of the positive electrode sheet is 0.2% to 2%, and the length is 100nm to 2800nm; the content of silane-modified carbon nanotubes in the second sub-active material layer of the positive electrode sheet is 0.4% to 2%, and the length is 100nm to 3000nm; the content of silane-modified carbon nanotubes in the first sub-active material layer of the positive electrode sheet is 0.2% to 2%, and the length is 100nm to 2800nm.
5. The electrode sheet according to claim 2, characterized in that: The electrode sheet is a negative electrode sheet; the content of silane-modified carbon nanotubes in the third sub-active material layer of the negative electrode sheet is 0.2% to 2.5%, and the length is 100nm to 3000nm; the content of silane-modified carbon nanotubes in the second sub-active material layer of the negative electrode sheet is 0.4% to 2.5%, and the length is 100nm to 3000nm; the content of silane-modified carbon nanotubes in the first sub-active material layer of the negative electrode sheet is 0.2% to 2.5%, and the length is 100nm to 3000nm.
6. The electrode sheet according to claim 1, characterized in that: The silane-modified carbon nanotubes include carbon nanotubes and a silane coupling agent covering at least a portion of the surface of the carbon nanotubes, wherein the silane coupling agent is connected to the carbon nanotubes via a covalent bond; The mass ratio of the carbon nanotubes to the silane coupling agent is (1.25-3.6):
1.
7. The electrode sheet according to claim 6, characterized in that: The length of the carbon nanotube is 100nm-5000nm, and the diameter is 2nm-60nm.
8. The electrode sheet according to claim 6, characterized in that: The silane coupling agent includes one or more of 1H, 1H, 2H, 2H perfluorooctyltrimethoxysilane, 1H, 1H, 2H, 2H perfluorooctyltriethoxysilane, 1H, 1H, 2H, 2H perfluorododecyltrimethoxysilane, 1H, 1H, 2H, 2H perfluorododecyltriethoxysilane, and heptadecafluorodecyltrimethoxysilane.
9. A method for preparing an electrode sheet according to any one of claims 1 to 8, characterized in that: The following steps are involved: Preparing a plurality of electrode slurries, and making the plurality of electrode slurries contain silane-modified carbon nanotubes; The plurality of electrode slurries are sequentially coated on at least a portion of the surface of at least one side of the current collector along the thickness direction of the current collector to form an active material layer including a plurality of sub-active material layers, and the electrode sheet is obtained by drying and pressing; The electrode slurry comprises active materials, a binder, silane-modified carbon nanotubes and a solvent.
10. A lithium battery, characterized in that: The electrode sheet comprises the electrode sheet according to any one of claims 1 to 8.
Citation Information
Cited By
Negative plate, preparation method thereof and battery
CN120674436A